2018
DOI: 10.1002/tox.22591
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particulate matter 2.5 on gene expression profile and cell signaling in JEG‐3 human placenta cells

Abstract: Particulate matter the environmental toxicant, with a diameter less than or equal to 2.5 μm (PM ) is a common cause of several respiratory diseases. In recent years, several studies have suggested that PM can influence diverse diseases, such as respiratory diseases, cardiovascular diseases, metabolic diseases, dementia, and female reproductive disorders, and unhealthy birth outcomes. In addition, several epidemiological studies have reported that adverse health effects of PM can differ depending on regional va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 46 publications
(74 reference statements)
0
5
0
Order By: Relevance
“…While the purpose of examining the two cohorts separately was in anticipation of replication of findings, inconsistency in findings may have resulted from differences (including demographic differences) in the study populations as well as variation in PM 2.5 exposure (such as source, composition, and magnitude) between the cohorts. PM 2.5 is a complex mixture of particles and its composition, which varies depending on seasons and regions, may lead to different outcomes, including gene expression ( Kim et al, 2018 ; Bell et al, 2007 ; Honkova et al, 2018 ). While the overall size of the study is large, study power may still preclude identification of significant differences in expression of some genes, particularly in the GAPPS study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the purpose of examining the two cohorts separately was in anticipation of replication of findings, inconsistency in findings may have resulted from differences (including demographic differences) in the study populations as well as variation in PM 2.5 exposure (such as source, composition, and magnitude) between the cohorts. PM 2.5 is a complex mixture of particles and its composition, which varies depending on seasons and regions, may lead to different outcomes, including gene expression ( Kim et al, 2018 ; Bell et al, 2007 ; Honkova et al, 2018 ). While the overall size of the study is large, study power may still preclude identification of significant differences in expression of some genes, particularly in the GAPPS study.…”
Section: Discussionmentioning
confidence: 99%
“…DNA adduct and DNA methylation) include signatures of DNA damage as well as genomic, epigenomic, proteomic, metabolomics and exposomic changes that occur in placenta following exposure to ambient air pollution and are closely related to placental function ( Luyten et al, 2018 ). While investigations of placental gene expression can further our understanding of placental functions that are affected by air pollution and related gene-environment interactions, few epidemiological and basic science studies have been conducted on PM 2.5 exposure and placental gene expression ( Luyten et al, 2018 ; Saenen et al, 2015 ; Whyatt et al, 1995 ; Kingsley et al, 2017 ; Kim et al, 2018 ; Deyssenroth et al, 2021 ). Findings from these studies indicated that exposure to PM 2.5 particles, which are small and can get deep into the lung and bloodstream, is associated with changes in placental expression of brain-derived neurotrophic factor ( BDNF ) ( Saenen et al, 2015 ), synapsin 1 ( SYN1 ) ( Saenen et al, 2015 ), cytochrome P450 1A1 ( CYP1A1 ) ( Whyatt et al, 1995 ), imprinted genes ( Kingsley et al, 2017 ), and genes related to amino acid transport and cellular respiration ( Deyssenroth et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…We will consider the evidence to date that air pollution disrupts the placental transcriptome and methylome profiles. Culturing of JEG-3 human placental cells in the presence of such PM affected genes involved in immune response, apoptosis regulation, calcium signaling pathway, steroid hormone biosynthesis, and cytokine-cytokine receptor interaction (Kim et al, 2018). Protein levels for mitogen activated protein kinases (MAPK) and COX2 were reduced in the PM 2 .…”
Section: Air Pollutionmentioning
confidence: 99%
“…Activation of pro-inflammatory signalling pathways, such as nuclear factor-kappa B (NF-κB) and mitogen-activated protein kinase (MAPK) pathways, has been implicated. 96 PM2.5 exposure can generate reactive oxygen species (ROS), leading to oxidative stress in cells. 97 Oxidative stress-related pathways, such as the Nrf2 (nuclear factor erythroid 2-related factor 2) pathway, may be activated in response to PM2.5.…”
Section: A Ir Pol Lu Tion a N D E N Dom Etr Iosismentioning
confidence: 99%
“…PM2.5 exposure can lead to inflammation through various mechanisms. Activation of pro‐inflammatory signalling pathways, such as nuclear factor‐kappa B (NF‐κB) and mitogen‐activated protein kinase (MAPK) pathways, has been implicated 96 . PM2.5 exposure can generate reactive oxygen species (ROS), leading to oxidative stress in cells 97 .…”
Section: Air Pollution and Endometriosismentioning
confidence: 99%